Two Is Company, Three Is Crowd: Report of Fatality from Ridding Triple (Seat) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Road traffic accident deaths are preventive form of deaths. In India, about 30,624 (22.4%) deaths in year 2011 was reported due to two-wheeler accidents. In this case series, we are reporting fatalities while driving two-wheeler with triple seat and reports pattern and distribution of injuries in such incidents. All were male and the age of individuals ranged from 30 to 55 years with mean age was 42 years. Analysing the pattern of injuries, in all cases there was head injury. Two-wheelers are unstable vehicle and require skill and balance while driving the vehicle. Riding the two-wheelers with three or more persons may cause crowding and increases the risk of accident.
Keywords: Road traffic; Accident; Death; Two-wheeler; Vehicle; Postmortem